Characteristics of the malay gardens from the historical perspective : exploring the theory and design concept / Nik Ismail Azlan and Siti Zubaidah Abu Kassim - Azlan, Nik Ismail; Abu Kassim, Siti Zubaidah (2012)
The early Malay gardens can traced from within the Malay World (Alam Melayu) or within the Malay Archipelago (Melayu Nusantara). It started from the grounds of the Malay Sultanates as the rulers have the means and might to create a place for their pleasure and leisure. Later on the gardens were initiated by the aristocrats and the common people as time progressed. Several descriptions of the Malay gardens were found from the books such as Bustanul Salatin (The Sultan Gardens), The Malay Annals and the description of the palace grounds such as Tanah Serendah Sekebun Bunga, Kebun Menseta, Forbidden Garden (Taman Larangan). These gardens were adorned with local plant species either from existing growth or planted to meet the needs of the owners. The plants species were utilised for their functions as herbal and medicinal values, food consumption, culinary delights, naming of children after the flowers and as a separation of boundary lines. Many of these plants species within the Malay gardens were selected and planted based upon their owners‟ needs or from the knowledge from sources such as Koran and medicinal healers. These gardens were based from the concept of outdoor living in harmony with God‟s creation that utilised local biodiversity. Apart from plants species many facilities and utilities suchs para (trellis) wakaf (gazebos), pots and jars, fishing gears and mats were part of elements of these early gardens especially around the common people compunds. However, due to the passing of time many of these gardens and their characteristics have been lost due to neglect and abandonement.